(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study was motivated by the difficulties first-year students experience in adjusting, particularly in terms of adapting, making friends, and understanding new learning patterns. In this context, self-efficacy was hypothesized to play a crucial role. This study aimed to examine the relationship between self-efficacy and adjustment among first-year undergraduate students at Battuta University. A quantitative approach was employed using a disproportionate stratified random sampling technique. The respondents consisted of 227 students. Data were collected using a Likert scale instrument and subsequently analyzed using the Pearson Product-Moment correlation technique. The analysis results indicated a correlation coefficient of r = 0,243, suggesting a positive and significant relationship between the two variables. However, this study is limited by its exclusive focus on internal factors (self-efficacy) without incorporating external factors, such as social support. Therefore, it is recommended that the university establish orientation or counseling programs focused on enhancing the self-efficacy of newly enrolled students, and that future researchers explore other external variables.